A Retrospective Study on Previously Untreated Non-metastatic Breast Cancer Patients at a Tertiary Care Hospital - Elahi, Md Quadrat E; Islam, Md Azizul; Sarwar, SM Rahid; Sarkar, Fatima (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: The combination of adoxorubicin and cyclophosphamide (AC) followed by a taxane (Docetaxel or Paclitaxel) and epirubicin and cyclophosphamide (EC) followed by a taxane (Docetaxel or Paclitaxel) is a standard regimen for breast cancer patients. In this study, we compared the three-year overall survival (OS) and progression free survival (PFS) of a patient with previously untreated non-metastatic breast cancer patients. Objectives: To find out the overall survival and progression free survival among previously untreated non-metastatic breast cancer patients after standard chemotherapy. Methods: Fifty-six patients received four cycles of doxorubicin at a dose of 60mg/m2 and cyclophosphamide at a dose of 600 mg/m2 followed by four cycles of paclitaxel at a dose of 175mg/m2. Thirteen patients received AC followed by four cycles of docetaxel at a dose of 75mg/m2. Twenty-one patients received four cycles of epirubicin (75mg/m2) and cyclophosphamide (600mg/m2), followed by four cycles of paclitaxel (175mg/m2). Twelve patients were given EC followed by four cycles of docetaxel (75mg/m2). Results: The four groups of patients had similar characteristics. Overall survivalafter three years was 92% in AC followed by paclitaxel, 98% in AC followed by docetaxel, 95% and 97% in EC followed by paclitaxel and docetaxel respectively. One year of PFS in AC followed by paclitaxel and docetaxel was 98% and 100% respectively whereas in EC followed by paclitaxel and docetaxel were 98% and 98% respectively. The four arms had 96%, 98%, 97% and 96% PFS after two years respectively. This research also revealed that four chemotherapy regimens had three-year survival rates of 93%, 98%, 93% and 96% respectively. Conclusion: AC or EC followed by taxane regimens well suitable regimens for the population of patients with previously untreated non-metastatic breast cancer patients. The findings show the need for continued observation as well as taking into account the treatment of other patients throughout different periods. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 11-14